Species composition of harmful entomofauna of agrobiocenosis of winter wheat in the Right-Bank of Forest-Steppe of Ukraine - Стригун, О. О.; Судденко, Ю. М. (Scientific Progress & Innovations, 2016)
We clarified the species composition of insects-phytophagous of winter wheat agrobiocenosis in the Right-Bank of Forest-Steppe of Ukraine. According to the results of monitoring of wheat entomocomplex we found 55 species of harmful insects from 19 families that in one way or another can damage the crop. The order Coleoptera was characterized by the highest species diversity. The results of the study found that the main and most dangerous pests that cause significant damage in the Right-Bank of Forest-Steppe is a complex of pests ears: aphids, wheat bugs, wheat chafers, thrips, cereal ground beetle.